Pemberdayaan Sekolah Luar Biasa (SLB) Banyumas melalui Pelatihan Teknologi Asistif Brailltek untuk Pembelajaran Mandiri - Sevia Indah Purnama; Adanti Wido Paramadini; Irmayatul Hikmah; Dodi Zulherman; Afin Muhammad Nurtsani; Rizki Amalia Pratiwi; Shinta Romadhona (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
Visually impaired students in Banyumas face significant challenges in accessing inclusive education due to the scarcity of adaptive learning media. Most students rely heavily on conventional Braille and constant teacher assistance, which hinders their independent learning capabilities. This community service aims to empower teachers and students at SLB Kuncup Mas Banyumas through the socialization and training of BraillTek, a bilingual RFID-based assistive device designed to support independent literacy. The method employed was a participatory approach involving 30 participants, consisting of teachers and students. The activities were conducted on December 9, 2025, encompassing socialization of disability rights, direct demonstration of the device, and hands-on training where students practiced using BraillTek while teachers were introduced to AI-based educational tools. The results indicated high program effectiveness, with evaluation data showing that 100% of participants agreed the material was highly relevant to their needs. Students demonstrated the ability to operate the device independently after a single session, effectively learning vocabulary without constant supervision. The program successfully introduced a viable solution for inclusive education, significantly reducing student dependence on teachers and improving teacher competency in utilizing assistive technology.